Development of Pancasila Values in Facing the Industrial Age 5.0 in the Community of Poka Village, Teluk Ambon City, Ambon City - Wa Markani; L. M. Metekohy; Jumiati Tuharea (CV. Rayyan Dwi Bharata, 2023)
The development of the era goes hand in hand with the development of technology and information so that modernity can no longer be avoided in this Era of Society 5.0, so that people now only memorize Pancasila but do not understand the meaning contained in it, the purpose of this research is 1. To develop Pancasila values in the environment society in facing the challenges of industry 5.0 2. factors influencing the development of Pancasila values in the industrial era 5.0 3. inhibiting factors in the development of Pancasila values in the industrial era 5.0. This study uses a qualitative approach and data collection techniques in this study using observation, interviews and using qualitative data analysis techniques. The results of this research show that there are still many people who do not understand and develop Pancasila values in society.